2010
DOI: 10.1007/s12105-010-0213-3
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Calcifying Odontogenic Cyst: A Case Report and Review of the Literature

Abstract: The peripheral calcifying odontogenic cyst (PCOC) accounts for less than 25% of the cases of calcifying odontogenic cysts and most commonly appears as a nodule on the gingiva. This paper aims to present both a case report of a PCOC located in the left vestibular maxilla as well as a review of the English-language literature. An 11-year-old female patient presented a swelling in the vestibular region of teeth 12 and 13. Periapical and panoramic radiographs demonstrated irregular calcification. Surgical excision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 21 publications
4
24
0
5
Order By: Relevance
“…[67] It is usually present as a slowly enlarging asymptomatic mass with smooth surface in the gingiva or alveolar mucosa. [9] The clinical differential diagnosis of ECCOT includes common gingival growths of non-neoplastic nature and other peripheral odontogenic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[67] It is usually present as a slowly enlarging asymptomatic mass with smooth surface in the gingiva or alveolar mucosa. [9] The clinical differential diagnosis of ECCOT includes common gingival growths of non-neoplastic nature and other peripheral odontogenic tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Resende et al [8], in their review of 44 well-defined cases of peripheral CCOT, also found a slight predilection for females and the anterior region. However, they found a similar distribution throughout the maxillary (40.9%) and mandible (47.7%) regions.…”
Section: Discussionmentioning
confidence: 99%
“…Não existe predileção por sexo ou etnia. Sem diferença significativa de localização entre maxila ou mandí-bula, o TOCC apresenta-se comumente na região anterior [3][4][5] . No presente caso, a lesão desenvolveu-se em região anterior de maxila e foi diagnosticada na terceira década de vida, estando em concordância com um relevante estudo que avaliou 215 casos de TOCC intraósseo, no qual 50% dos casos associados a odontoma estavam localizados em região de incisivo a canino e 60% destes pacientes foram diagnosticados na segunda ou terceira década de vida 4 .…”
Section: Discussão E Conclusõesunclassified
“…Em alguns casos pode provocar aumento de volume e desconforto local. O TOCC intraósseo apresenta-se como imagem radiotransparente geralmente unilocular, podendo apresentar calcificaç ões internas irregulares e associação com outros tumores odontogénicos, como o odontoma [3][4][5] .…”
Section: Introductionunclassified